2021
DOI: 10.1002/1878-0261.13032
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine induces podocyte apoptosis by regulating miR‐1929‐5p expression through c‐Myc, DNMT1 and EZH2

Abstract: Chronic kidney disease (CKD) is a common and complex disease in kidneys which has been associated with an increased risk of renal cell carcinoma. Elevated homocysteine (Hcy) levels are known to influence the development and progression of CKD by regulating podocyte injury and apoptosis. To investigate the molecular mechanisms triggered in podocytes by Hcy, we used cbs+/− mice and observed that higher Hcy levels increased the apoptosis rate of podocytes with accompanying glomerular damage. Hcy‐induced podocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…HHcy has also been reported to be associated with acceleration of CKD progression. The relevant study demonstrated that Hcy promotes podocytes apoptosis through regulation of the epigenetic modifiers DNA methyltransferase 1 (DNMT1) and enhancer of zeste homolog 2 (EZH2), which are recruited by c-Myc to miR-1929-5p promoter and silence miR-1929-5p expression [ 48 ] ( Figure 3 ). Hcy also had a role in the development of acute kidney injury in cbs +/− mice.…”
Section: Methionine and Its Metabolite Homocysteinementioning
confidence: 99%
“…HHcy has also been reported to be associated with acceleration of CKD progression. The relevant study demonstrated that Hcy promotes podocytes apoptosis through regulation of the epigenetic modifiers DNA methyltransferase 1 (DNMT1) and enhancer of zeste homolog 2 (EZH2), which are recruited by c-Myc to miR-1929-5p promoter and silence miR-1929-5p expression [ 48 ] ( Figure 3 ). Hcy also had a role in the development of acute kidney injury in cbs +/− mice.…”
Section: Methionine and Its Metabolite Homocysteinementioning
confidence: 99%
“…Under the interaction of DNMT1 and HMT G9a, homocysteine inhibits the expression of reticulo-oxidoreductase 1α (ERO1α), activates the occurrence of endoplasmic reticulum stress and hepatocyte apoptosis, causing liver injury [ 152 ]. In addition, DNA methylases are also involved in the progression of chronic kidney disease to renal cell carcinoma [ 153 ].…”
Section: Types Of Chromatin Modifiersmentioning
confidence: 99%
“…Excessive apoptosis may lead to disease. Lin Xie found that homocysteine promotes podocyte apoptosis by regulating epigenetic modifiers DNMT1 and EZH2, which is accompanied by glomerular damage, leading to the progress of CKD ( Xie et al, 2021 ). Nan Yu found that podocytes are an important part of renal glomerular filtration barrier, and podocyte dysfunction and apoptosis are important factors leading to the progress of chronic kidney disease (CKD) ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%